The “crossover effect” of COVID-19 in pregnancy on the infant microbiome - Ignatyeva, O.; Daniel, V.; Zelenova, E.; Cherdakli, A.; Bolashova, E.; Matkava, L.; Shegurova, A.; Volkov, M.; Zagainova, A.; Kashtanova, D.; Ivanov, M.; Bembeeva, B.; et al. (Frontiers in Microbiology, 2025)
BackgroundThe COVID-19 pandemic has had a significant impact on public health. However, the impact of COVID-19 infection during pregnancy on the microbiome of the mother and her newborn child still remains poorly understood.MethodsThis study involved 94 mother-child pairs whose mothers had COVID-19 during pregnancy and 44 newborns as a control group recruited in 2018. Stool samples were collected from women before delivery and from infants at 5–7 days after birth and used for 16S rRNA sequencing.ResultsWe found that the microbiomes of infants exposed in utero to COVID-19 showed decreased microbial diversity and richness. Moreover, we observed a higher inter-sample variability between infant samples in the case group, which might suggest destabilization of their microbiomes. Neither alpha- nor beta-diversity metrics differed significantly between the groups depending on the trimester when the mother contracted COVID-19. Thus, the timing of prenatal COVID-19 exposure had no effect on the infant gut microbiome.ConclusionCOVID-19 during pregnancy can significantly compromise the establishment of the infant gut microbiome presumably by disrupting the mother’s microbiome.